Comparison of analgesic effects between betamethasone and dexamethasone in total knee arthroplasty: a prospective randomized controlled trial - Qin, Kai; Sun, Xiangxiang; Dou, Qunli; Li, Bowei; Bai, Guoyang; Sun, Xiaobo; Ma, Jianbing; Xu, Chao; Huang, Yuanchi (Frontiers in Medicine, 2025)
BackgroundCorticosteroids such as dexamethasone and betamethasone are widely used for local infiltration analgesia in total knee arthroplasty (TKA). However, the analgesic efficacy of these two glucocorticoids in TKA cocktail therapy remains unknown. Therefore, this study aims to compare the analgesic efficacy and safety of betamethasone and dexamethasone in TKA through a prospective randomized controlled trial (RCT).MethodsA total of 120 patients were randomly assigned to three groups: Control (Con) group, Dexamethasone (Dex) group and Betamethasone (Beta) group. The primary outcome was the postoperative visual analog scale (VAS); the secondary outcomes were the knee range of motion (ROM).ResultsCompared with the Con group, the VAS scores of the Dex group during walking were decreased significantly at 12 and 24 h postoperatively, while the Beta group showed a decrease at 12, 24, 48 h and 2 weeks postoperatively. In terms of dynamic VAS scores at 12, 24, 48 h and 2 weeks postoperatively the Beta group was superior to the Dex group. At 48 h and 2 weeks postoperatively, the ROM in the Beta group was better than Dex group. There were no significant differences among the three groups in terms of inflammatory markers and incidence of postoperative adverse event.ConclusionOur prospective RCT demonstrates that betamethasone exhibits better analgesic effects than dexamethasone in the cocktail therapy of TKA and does not incur additional complications, providing a medication basis for the local application of glucocorticoids in TKA.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR2300072533.